2017
DOI: 10.1038/s41598-017-18302-0
|View full text |Cite
|
Sign up to set email alerts
|

Hierarchical Porous Chitosan Sponges as Robust and Recyclable Adsorbents for Anionic Dye Adsorption

Abstract: Biomass waste treatment and detrimental dye adsorption are two of the crucial environmental issues nowadays. In this study, we investigate to simultaneously resolve the aforementioned issues by synthesizing chitosan sponges as adsorbents toward rose bengal (RB) dye adsorption. Through a temperature-controlled freeze-casting process, robust and recyclable chitosan sponges are fabricated with hierarchical porosities resulted from the control of concentrations of chitosan solutions. Tested as the adsorbents for R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
77
1
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 106 publications
(92 citation statements)
references
References 45 publications
12
77
1
2
Order By: Relevance
“…The R L values 0.91 and 0.74 obtained for MG and RB4 dyes respectively is a proof of favourable adsorption of the dyes onto the adsorbent. Similarly, the empirical parameter, n of the Freundlich isotherm indicates surface heterogeneity of the adsorbent, while its value confirms the favourability of adsorption process [27]. The parameters obtained for Tempkin isotherm fit is also in support of surface heterogeneity and the interaction between the adsorbent and the dye molecules, the adsorption heat obtained for MG is higher than that of RB4 whereas the binding constant is higher in the latter than the former, justifying the lower adsorption capacity obtained for RB4.…”
Section: Adsorption Isothermssupporting
confidence: 52%
“…The R L values 0.91 and 0.74 obtained for MG and RB4 dyes respectively is a proof of favourable adsorption of the dyes onto the adsorbent. Similarly, the empirical parameter, n of the Freundlich isotherm indicates surface heterogeneity of the adsorbent, while its value confirms the favourability of adsorption process [27]. The parameters obtained for Tempkin isotherm fit is also in support of surface heterogeneity and the interaction between the adsorbent and the dye molecules, the adsorption heat obtained for MG is higher than that of RB4 whereas the binding constant is higher in the latter than the former, justifying the lower adsorption capacity obtained for RB4.…”
Section: Adsorption Isothermssupporting
confidence: 52%
“…This difference in the amount of water uptake was only because of the properties of aerogels: chemical functional groups on the nanofibers, high specific surface area and open porosity of the material. This insoluble behavior of the material in acidic and alkaline medium can provide opportunities to utilize the aerogel in reusable systems in applications like those reported …”
Section: Resultsmentioning
confidence: 99%
“…Highly porous chitosan‐based materials can offer potential chelating functional properties. Recently, Wang et al . demonstrated that highly porous chitosan foams with chelating amine functional groups can be a promising adsorbent material for anionic dyes from which the elution of dyes have been accomplished with alkaline treatment of the foams.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Além dessas características a quitosana ainda apresenta excelentes propriedades como: não toxicidade, biocompatibilidade, biodegradação, reatividade e capacidade de adsorção. Estudos envolvendo a modificação estrutural da quitosana e seus derivados têm sido amplamente realizados com o intuito de empregar esses materiais em uma gama de aplicações [10][11][12][13], com destaque na área de catálise [8,[14][15][16].…”
Section: Introductionunclassified